How virtual reality is making people 'well' again - Quesnel, Denise T. (World Economic Forum, 2017)
Research suggests that VR experiences can improve people's mental wellbeing.
Keywords: Riecke_2017; denise-quesnel; dissemination-4generalPublic; mediaCoverage